2017
DOI: 10.1002/mp.12290
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo study of the chamber-phantom air gap effect in a magnetic field

Abstract: Purpose The aim of this study was to examine the effect of sub-millimeter air gaps that may exist between an ionization chamber and solid phantoms when measurements are performed in a magnetic field. Methods Geant4 Monte Carlo simulations were performed using a model of a PTW 30013 Farmer chamber in a water phantom. Symmetrical and asymmetrical air gaps of various thicknesses were modeled surrounding the chamber, and the dose to the air cavity of the chamber was scored in each case. Magnetic fields were mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 12 publications
3
64
1
Order By: Relevance
“…Here the variation in kQitalicmag due to changes in the sensitive volume are looked at, and a resolution of the issue is sought through finding an optimal orientation with respect to the magnetic field. Air gaps surrounding the chamber have been shown to cause several percent change in the chamber response . These changes are notable in plastic phantoms, and the issue is negligible when using a water phantom for ion chamber measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Here the variation in kQitalicmag due to changes in the sensitive volume are looked at, and a resolution of the issue is sought through finding an optimal orientation with respect to the magnetic field. Air gaps surrounding the chamber have been shown to cause several percent change in the chamber response . These changes are notable in plastic phantoms, and the issue is negligible when using a water phantom for ion chamber measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Although a systematic difference appears to exist between the two phantoms, the combined uncertainty in this comparison is approximately 0.4% ( k = 1), thus no statistical significance can be ascribed. Elucidation of this expected small effect will require the MC simulation of air gaps surrounding Aerrow in various configurations (i.e., gap thickness and symmetry, B ‐field magnitude, and detector orientation with respect to the radiation and B ‐fields), in‐line with the chamber‐focused study by O'Brien and Sawakuchi …”
Section: Discussionmentioning
confidence: 91%
“…34 The appropriateness of IC-based dosimetry in conventional solid phantoms in the presence of a B-field has been investigated by several groups, and, to date, have identified the effect of the clearance air gap present between the chamber and phantom as a source of hindering perturbation. 7,[16][17][18]65,66 Most recently, O'Brien and Sawakuchi 18 studied this effect by simulating a PTW 30013 IC in water with surrounding symmetric and asymmetric air gaps of various thicknesses in the presence of B-fields in the range of (0.35-1.5) T using MC. They concluded that the effect was not attributable to the electron return effect, but rather to the loss of electron contributions originating within the air gap, which is not entirely compensated for by more distant electrons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations